2018
DOI: 10.2147/hiv.s163269
|View full text |Cite
|
Sign up to set email alerts
|

HIV awareness and safe sexual behaviors among female sex workers in Kathmandu valley of Nepal

Abstract: PurposeKnowledge on HIV and safe sex practices are the main determinants for the prevention and control of HIV/AIDS transmission. The aim of this study was to assess HIV awareness and safe sexual behavior among the female sex workers (FSWs) in the Kathmandu valley of Nepal.MethodsThe study was based on data secondary to Integrated Biological and Behavioral Surveillance surveys of 2093 FSWs in Kathmandu valley from 2006 to 2015. Bivariate and multivariate logistic regression models were used to identify the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…On the contrary, research in Kathmandu, Nepal revealed that knowledge of FSWs was very low, but condom use of clients significantly increased [17]. A study which participated 237 FSWs in Somalia showed that only 6,9% who was able to answer correctly basic knowledge on HIV/AIDS, and 38.4% who ever heard about sexually transmitted infection disease [18].…”
Section: Introductionmentioning
confidence: 98%
“…On the contrary, research in Kathmandu, Nepal revealed that knowledge of FSWs was very low, but condom use of clients significantly increased [17]. A study which participated 237 FSWs in Somalia showed that only 6,9% who was able to answer correctly basic knowledge on HIV/AIDS, and 38.4% who ever heard about sexually transmitted infection disease [18].…”
Section: Introductionmentioning
confidence: 98%
“…In Nepal, there are many at-risk groups in some specific locations (the Pokhara Valley and Kathmandu), with a high number of drivers of disease transmission like increased economic activities (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). These at-risk groups include people who inject drugs, female sex workers, men who have sex with men and labour migrants (17).…”
Section: Introductionmentioning
confidence: 99%
“…There has been previous descriptive research in the Kathmandu Valley in Nepal into key risk factors and prevalence trends (7)(8)(9)17), however, more detailed analytic approaches to investigate sociodemographic and behavioural factors are currently lacking for this setting. Previous behavioural studies have also shown that there are multiple risk factors that act as determinants for HIV and other sexually transmitted diseases within other areas of Nepal (10,11), such as social class and education level (21).…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, there are many at-risk groups in some speci c locations (the Pokhara Valley and Kathmandu), with a high number of drivers of disease transmission like increased economic activities (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). These at-risk groups include people who inject drugs, female sex workers, men who have sex with men and labour migrants (17).…”
Section: Introductionmentioning
confidence: 99%
“…There has been previous descriptive research in the Kathmandu Valley in Nepal into key risk factors and prevalence trends (7)(8)(9)17), however, more detailed analytic approaches to investigate socio-demographic and behavioural factors are currently lacking for this setting. Previous behavioural studies have also shown that there are multiple risk factors that act as determinants for HIV and other sexually transmitted diseases within other areas of Nepal (10,11), such as social class and education level (21).…”
Section: Introductionmentioning
confidence: 99%